β-LACTOGLOBULIN GENETIC VARIANTS IN BROWN-SWISS DAIRY CATTLE AND THEIR ASSOCIATION WITH MILK YIELD AND QUALITY TRAITS - Unsal Dogru (Journal of Animal and Plant Sciences, 2015)
Milk protein polymorphism such as β-Lactoglobulin (β-Lg) of Brown-Swiss dairy cows were investigated in this study. The relationships between milk protein genotypes and some milk production traits were determined. Genetic variants of milk protein were identified by horizontal starch-gel electrophoresis containing mercaptoethanol and urea. The allelic frequencies of A and B were found to be 0.375 and 0.625 respectively. Milk production traits chosen in relation to β-Lg variants were: actual milk yield, 305 d milk yield, actual fat yield, 305 d fat yield, fat percentage in milk, lactation length. Genotype frequencies were in accordance with the Hardy-Weinberg equilibrium. The effect of β-Lg genotypes on milk production traits were analyzed using a general linear model (GLM). There was no significant association between different genotypes of β-Lg and milk production traits of the analyzed cows.
Keywords: β-Lactoglobulin; protein polymorphism; dairy cow; milk production traits